2011
DOI: 10.1155/2011/529648
|View full text |Cite
|
Sign up to set email alerts
|

Heat Shock Proteins in Association with Heat Tolerance in Grasses

Abstract: The grass family Poaceae includes annual species cultivated as major grain crops and perennial species cultivated as forage or turf grasses. Heat stress is a primary factor limiting growth and productivity of cool-season grass species and is becoming a more significant problem in the context of global warming. Plants have developed various mechanisms in heat-stress adaptation, including changes in protein metabolism such as the induction of heat shock proteins (HSPs). This paper summarizes the structure and fu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
58
0
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
3
2

Relationship

1
8

Authors

Journals

citations
Cited by 87 publications
(61 citation statements)
references
References 109 publications
(130 reference statements)
1
58
0
2
Order By: Relevance
“…In the current study, the candidate gene marker for CAB was found to be significantly associated with overall visual quality in the 2015 Georgia drought trial and membrane stability in the 2014 Georgia summer trial. Allelic variations in chlorophyll binding proteins were associated with differences in key agronomic traits in barley (Xia et al, 2012), and light-harvesting CAB proteins have also been implicated in abscisic acid signaling (Xu et al, 2011), indicating that genetic differences in chlorophyll binding proteins may have far-reaching impacts. Furthermore, CAB has been shown to have enhanced expression under drought conditions in more stress tolerant lines of barley (Hordeum vulgare L.), rice (Oryza sativa L.), and wheat (Triticum aestivum L.), indicating that CABs are an important aspect of acquired stress tolerance (Gorantla et al, 2007;Guo et al, 2009;Peng et al, 2009).…”
Section: Frymentioning
confidence: 99%
See 1 more Smart Citation
“…In the current study, the candidate gene marker for CAB was found to be significantly associated with overall visual quality in the 2015 Georgia drought trial and membrane stability in the 2014 Georgia summer trial. Allelic variations in chlorophyll binding proteins were associated with differences in key agronomic traits in barley (Xia et al, 2012), and light-harvesting CAB proteins have also been implicated in abscisic acid signaling (Xu et al, 2011), indicating that genetic differences in chlorophyll binding proteins may have far-reaching impacts. Furthermore, CAB has been shown to have enhanced expression under drought conditions in more stress tolerant lines of barley (Hordeum vulgare L.), rice (Oryza sativa L.), and wheat (Triticum aestivum L.), indicating that CABs are an important aspect of acquired stress tolerance (Gorantla et al, 2007;Guo et al, 2009;Peng et al, 2009).…”
Section: Frymentioning
confidence: 99%
“…Candidate gene markers for CAB may help identify lines which are better able to maintain photosynthesis during unfavorable conditions and have improved stress tolerance. HSP26 belongs to the group of small heat shock proteins that are involved in stabilizing and refolding proteins damaged during stress events (Xu et al, 2011). PAL was associated with NDVI, CHL, and TQ in the 2014 Georgia summer trial and CHL in the 2015 New Jersey summer trials, indicating that this gene may be involved in maintaining a green turf canopy during temperature stress conditions.…”
Section: Frymentioning
confidence: 99%
“…Additionally, when the proteomes of these acclimatized plants were observed, proteins involved in amino acid metabolism, energy production, stress defence and secondary metabolism were differentially abundant. Xu et al ( 2011b ) also studied heat-shock proteins (HSPs) and their relation to heat tolerance in grasses, focusing on HSP role in heat tolerance, allowing essential cellular processes such as amino acid and protein metabolism, photosynthesis and carbon allocation to continue, thus allowing the survival of the plant.…”
Section: Forage Crop Proteomicsmentioning
confidence: 99%
“…On the other hand, climate warming directly impacts the dynamics of the terrestrial vegetation biomes by increasing the frequency, duration and severity of drought and heat stress [8][9][10][11], while other studies have suggested that climate warming tends to relax temperature constraints for plant growth [12,13]. Many studies assume that plants have an optimal threshold for growth and reproduction [14], suffering cold stress when temperatures are below this threshold, and heat stress when above [15]. Accordingly, we can deduce that when the in-situ temperature is suboptimal, climate warming may relax the temperature constraint for plant metabolism and promote its growth, while supraoptimal temperature conditions and the accompanying rise in the vapor pressure deficit and evaporation may damage the plant's cellular tissues [8,16,17].…”
Section: Introductionmentioning
confidence: 99%